Resilience against radicalization and extremism in schools: Development of a psychometric scale - Eldor, David S.; Lindholm, Karine; Chavez, Maria H.; Vassanyi, Sander; Badiane, Michelle O. I.; Yaldizli, Kemal; Frøysa, Petter; Haugestad, Christian A. P.; Kunst, Jonas R. (Frontiers in Psychology, 2022)
Practitioners, policymakers, and researchers alike have argued that the school environment can be both a risk and resilience factor for radicalization and extremism among youth, but little research has tested this directly. Against this background and using a cultural and community psychological approach, we developed a scale to measure resilience against radicalization and extremism in schools focusing on factors that can strengthen social cohesion. A total of 334 school pupils from mostly urban areas in Norway were recruited for this research, of which 233 passed an attention check and were retained for analyses. Participants completed a larger set of items that were derived from theory and the experiences of practitioners and were intended to measure resilience to radicalization and extremism. Exploratory factor analysis identified three dimensions: (1) the perception that the school treats pupils equally no matter their social backgrounds, (2) the perception of the school and its employees as attentive and proactive in meeting pupils’ anger resulting from social and political issues, and (3) the presence of mutual respect. In regression analyses, the equality dimension predicted lower extremist intentions and radicalization as well as four out of five extremism risk factors (i.e., lower anomie, symbolic and realistic threats, and relative deprivation). Mutual respect showed no significant effect, whereas school attentiveness positively predicted three risk factors as well as radicalism intentions and violent intentions, suggesting that such attentiveness may a response to these issues. In sum, the findings indicate that resilience against extremism in schools may be nurtured especially by creating an egalitarian school environment. Our study provides the first scale assessing such resilience in schools, which can be further tested and developed in future research.